Infection of 'Candidatus Phytoplasma Vitis' in a Hungarian Vineyard East of the Danube - Szathmáry, Erzsébet; Merkely, Balázs; Végh, Anita (GEORGIKON FOR AGRICULTURE, 2024)
In Hungary, two phytoplasma species are known to infect grapevines, the 'Candidatus Phytoplasma vitis' and the 'Ca. Phytoplasma solani'. The 'Ca. Phytoplasma vitis' is one of Europe's economically most important grapevine pathogens, as its infection can cause significant yield losses and even the death of infected vines. The 'Ca. Phytoplasma vitis' was first described in Hungary in 2013, and since then, it has been reported from grapevines and traveller's joys in several transdanubian counties, while east of the Danube, it has only been identified in a few cases in grapevines. In the summer of 2023, leaf yellows and rapid death of vine stocks were observed in Csongrád. After total nucleic acid extraction, nested PCR tests were carried out using universal phytoplasma primers (P1/P7 and fU5/rU3). All tested samples were positive for phytoplasma infection. Based on the results of the in silico RFLP analysis using Tru9I restriction endonuclease, the infection of 'Ca. Phytoplasma vitis' were determined, which pathogen has not yet been reported from grapevines in Csongrád-Csanád County.
Keywords: Vitis; grapevine; phytoplasma; PCR; Flavescence dorée